2019
DOI: 10.1002/ese3.489
|View full text |Cite
|
Sign up to set email alerts
|

A study on a near‐shore cantilevered sea wave energy harvester with a variable cross section

Abstract: A cantilevered piezoelectric coupled energy harvester with variable cross section is proposed to obtain the electric power from the longitudinal motion of the near‐shore sea wave. In order to describe the practical process of the sea wave energy harvesting, a mathematical model of the harvester is established based on Airy linear wave theory and Bessel equations to calculate the output charge, voltage, current, and power. Compared to traditional cantilever harvesters with uniform cross section, this harvesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…On the basis of the obtained results, it was confirmed that the most optimal cantilever section is the conical section, which significantly increases the efficiency of the structure. The modification of the cantilever harvester to obtain energy from the motion of sea waves is presented in [8]. A mathematical model was created through the Airy wave theory and the Bessel equations to calculate the stored power and the output charge.…”
Section: Vibration Problems In Electromechanical Energy Harvestingmentioning
confidence: 99%
“…On the basis of the obtained results, it was confirmed that the most optimal cantilever section is the conical section, which significantly increases the efficiency of the structure. The modification of the cantilever harvester to obtain energy from the motion of sea waves is presented in [8]. A mathematical model was created through the Airy wave theory and the Bessel equations to calculate the stored power and the output charge.…”
Section: Vibration Problems In Electromechanical Energy Harvestingmentioning
confidence: 99%
“…Wind-driven harvesters, in contrast to other harvesters, would not require a large land area due to their vertical design, making them easy to install in areas such as high terrain, mountains, and coastal areas. , Prevailing wind speed at a height of 80 m above-ground is greater than 6.9 m/s . Energy harvesting from wind close to the ground has various uses but has the disadvantages of being highly influenced by geography and weather as well as having a low output due to low wind speed.…”
Section: Introductionmentioning
confidence: 99%
“…The research results prove that the triangular cantilever substrate with a central triangular hole is the optimal structure style to collect more energy in a wider low‐frequency vibration environment. Zhang et al 40 proposed a piezoelectric coupling energy collector of a variable cross‐section cantilever to harvest offshore wave energy. Xie et al 41 developed a tapered cantilever piezoelectric energy harvester which has a higher efficiency of energy harvesting than the existing rectangular cantilever.…”
Section: Introductionmentioning
confidence: 99%